Combining CRP testing and patient information leaflets to safely reduce antibiotic use for acute respiratory tract infections in adults: Protocol for the 2CARE randomised controlled trial in Kyrgyz primary care - Azamat Akylbekov; Elvira Isaeva; Maamed Mademilov; Volkert Siersma; Torsten Risør; Sif Helene Arnold; Jesper Kjærgaard; Nandini Sreenivasan; Ahmad Wesal Zaman; Talant Sooronbaev; Rune Munck Aabenhus (PLoS ONE, 2026)
Background Antimicrobial resistance (AMR) is a major health challenge in Kyrgyzstan, where acute respiratory tract infections (ARTIs) are common and frequently treated with antibiotics. Although C-reactive protein (CRP) point-of-care testing can support rational prescribing, there is no consensus on safe CRP thresholds for adults. Patient information leaflets (PILs) may further reduce inappropriate antibiotic use by improving understanding of ARTIs and addressing expectations for antibiotics. The 2CARE trial evaluates whether combining PILs with CRP testing can safely reduce antibiotic use among adults with ARTIs in Kyrgyz primary care. Methods 2CARE is a multicentre, open-label, individually randomised controlled trial conducted in 15 primary healthcare centres in Kyrgyzstan. Adults aged 18–70 years with acute respiratory symptoms (<14 days) are randomised 1:1 to receive a PIL or no PIL, and independently 1:1:1 to one of three CRP cut-off levels (20, 40, or 60 mg/L), yielding six parallel groups. Primary outcomes are: (1) total antibiotic use within 21 days, and (2) hospital admission within 21 days. Secondary outcomes include baseline antibiotic prescribing, re-consultations, recovery, hospital referral, antiviral use, and mortality. Analyses will follow the intention-to-treat principle, with per-protocol analysis for non-inferiority, using regression models and generalized estimating equations. A total sample of 1,050 participants provides 90% power for both primary comparisons. Discussion This trial will generate evidence on the effectiveness of PILs in reducing antibiotic use and establish safe CRP thresholds for adults with ARTIs in a low-resource setting. Findings will inform antimicrobial stewardship policies and guide national CRP implementation in Kyrgyzstan. Trial registration ClinicalTrials.gov Identifier: NCT07261969 .